Implementasi Penggunaan Media Elektronik Smart TV pada Pembelajaran IPS Kelas VIII SMP Ulil Albab Mojo Kediri - Mohamad Harun Rifai; Dita Hendriana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe the implementation of electronic media Smart TV in Social Science (IPS) learning at SMP Ulil Albab Mojo Kediri. The study employed a descriptive qualitative approach, using interviews, observations, and documentation as data collection techniques. The findings indicate that the use of Smart TV has a positive impact on students' enthusiasm, motivation, and comprehension in IPS learning. Visuals and animations presented through Smart TV attract students' attention, enhance learning focus, and provide stronger conceptual understanding. However, challenges were also identified, such as unstable internet connection, weak electricity supply, and misuse by students. School management strategies and teacher readiness are crucial factors for successful implementation. With proper management, Smart TV can serve as an interactive, efficient, and relevant learning medium to meet the challenges of digital-era education.